Distribution Mapping Of House Type, House Age And Sick Building Syndrome Among Work-From-Home Workers By Using A GIS-based Approach - Nur Afrina Miza, Aziz Nasatioun; Mohammad Adam, Adman; Norsaffarina, Aziz; Syarifuddin, Misbari (Malaysian Association of Environmental Health (MAEH), 2023)
Sick Building Syndrome (SBS) is a condition that commonly affects building occupants, and it is characterized by various symptoms related to the indoor climate, including indoor air quality, inadequate lighting, maintenance efficiency, and ventilation. This study aims to create distribution maps of housing infrastructure in Kuantan based on house type and house age and determine the prevalence of SBS among work-from-home (WFH) workers in the Kuantan study areas. A geospatial-based approach was employed to visualize the distribution of the general SBS symptoms among 112 WFH workers using a questionnaire that combined the Swedish MM040 and ICOP2010 questionnaires. The results obtained from the geospatial distribution maps revealed that a significant number of WFH workers in Kuantan experienced SBS symptoms, and most of them resided in terrace houses that were more than ten years old.